2015
DOI: 10.4250/jcu.2015.23.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Global Right Ventricular Longitudinal Strain Predicts Long-Term Adverse Outcomes in Patients with Pulmonary Arterial Hypertension

Abstract: BackgroundNew 2-dimensional strain echocardiography enables quantification of right ventricular (RV) mechanics by assessing global longitudinal strain of RV (GLSRV) in patients with pulmonary arterial hypertension (PAH). However, the prognostic significance of impaired GLSRV is unclear in these patients.MethodsComprehensive echocardiography was performed in 51 consecutive PAH patients without atrial fibrillation (40 females, 48 ± 14 years old) with long-term follow-up. GLSRV was measured with off-line with vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 28 publications
2
56
0
3
Order By: Relevance
“…Puwanant et al reported that the longitudinal deformation of RV free wall in patients with PH is significantly decreased compared to control subjects. Park et al reported that RVLS using echocardiographic velocity vector imaging significantly correlated with conventional echocardiographic RV function parameters. In this study, RVLS assessed with CMR‐HDA positively correlated with RVEDV and RVESV, whereas RVLS was inversely correlated with RVEF and RVCI in patients with CTEPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Puwanant et al reported that the longitudinal deformation of RV free wall in patients with PH is significantly decreased compared to control subjects. Park et al reported that RVLS using echocardiographic velocity vector imaging significantly correlated with conventional echocardiographic RV function parameters. In this study, RVLS assessed with CMR‐HDA positively correlated with RVEDV and RVESV, whereas RVLS was inversely correlated with RVEF and RVCI in patients with CTEPH.…”
Section: Discussionmentioning
confidence: 99%
“…Strain, defined as tissue deformation as the myocardium contracts in systole as a result of sarcomere shortening as measured with echocardiography or CMR, now have been directly assess ventricular mechanics and function. Although the impaired right ventricular longitudinal strain (RVLS) measured with 2‐dimensional strain echocardiography was significantly associated with adverse clinical events and deaths in patients with pulmonary hypertension (PH), tissue character such myocardial edema, fibrosis cannot be obtained by echocardiography at the same time. CMR Myocardial tagging has been established as the standard of reference for accurate measurement of regional ventricular strain and both left and RV strain reduced in patients with PH, however, CMR tagging requires special scanning and post processing.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the additional value in left heart failure and valvular heart disease, RV plays a pivotal role in the regulation and compliance of the pulmonary vascular system [18,19] With exercise, RV dysfunction results in the increase of vascular pressures and impairment of oxygen exchange. However, studies focusing on RV function and functional capacity in apparently healthy subjects remain lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Severe BPD may result in chronic pulmonary artery hypertension (PAH) and gradual dilatation as well as hypertrophy of the right ventricle (RV)1)2)3)4)5) that can lead to RV dysfunction and right heart failure. It is associated with poor prognosis 3)4)5)6)7)8)…”
Section: Introductionmentioning
confidence: 99%